Development Of Animation Based Quiz Media Themes Of Animals To Improve Expressive Language Skills - Rere Setianingsih; Ahmad Yani; Asep Mulyana; Alfiyanti Nurkhasyanah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
The use of media that is still low at the level of children's expressive language skills makes researchers create media that aims to improve graphic language skills of children 4-5 years old by making magazines as children's worksheets. The research method used is by using research and development methods with data collection techniques through data collection, product design, and produce results which are then processed into data which is then analyzed. Based on the study results, the expressive language skills of the students of Play Group PAUD Harapan Bangsa Cirebon Regency after the trial showed an increase of 22.50% with the outcome of 78.50%, namely in the very well developed category. Animated animal-themed quiz game contains animations (moving pictures), including sub-themes of animal types, animal characteristics, and animal food. Therefore, creating an animated quiz media based on animal themes can improve the expressive language skills of early childhood.